Оцінка ефективності використання загального знеболювання для профілактики стоматологічних захворювань у дітей-інвалідів з хворобами центральної нервової системи, захворюваннями системи крові, системи дихання та психічними розладами - Гавриленко, Марина Аркадіївна; Gavrilenko, M. A. (My University, 2017)
Діти з інвалідністю, що хворіють на хвороби центральної нервової системи, захворювання крові, дихання та з психічними розладами, мають високий відсоток стоматологічних захворювань [1]. Деякі профілактичні заходи, як-от: регулярну професійну гігієну порожнини рота, герметизацію фісур, ремінералізуючу терапію зубів — майже неможливо виконати, зважаючи на стан здоров’я дітей-інвалідів, їхню неконтрольовану поведінку та стоматофобію [2]. Ми запропонували використання загального знеболювання зі штучною вентиляцією легенів для проведення профілактики стоматологічних захворювань дітям з інвалідністю нарівні з санацією порожнини рота [3]. Мета: проведення профілактики стоматологічних захворювань і підвищення ефективності надання стоматологічної допомоги дітям з інвалідністю [4], які хворіють на хвороби центральної нервової системи, захворювання крові, дихання та з психічними розладами, з використанням загального знеболювання [5]. Introduction. Children with disabilities suffering from diseases of the central nervous system, blood diseases, respiration and mental disorders have a high percentage of dental diseases. Conducting preventive measures, namely: regular professional oral hygiene, fissure sealing, remineralizing teeth therapy, is almost impossible to fulfill, taking into account the health status of children with disabilities, their uncontrolled behavior and dentistry. We proposed the use of general anesthesia with artificial ventilation of the lungs for the prevention of dental diseases for children with disabilities, along with the sanitation of the oral cavity. Materials and methods. 200 disabled children with diseases of the central nervous system, mental disorders, diseases of the blood system, respiratory organs related to 3, 4, 5 classes of physical status according to the classification of ASA, aged 2 to 15 years. Results. Improvement of indices of hygiene indexes in the nearest and distant terms after carrying out of the prophylactic complex in groups, which were carried out professional brushing of teeth and preventive measures under general anesthesia. The ideal preservation of the sealant and the smallest percentage of the development of fissure caries was noted in children with disabilities, which sealed the fissure under general anesthesia. Prophylactic closure of permanent teeth fissures in children with disabilities should be performed under general anesthesia in children of groups I and IV using composite photopolymeric sealants. The use of general anesthesia made it possible to carry out modern methods of prevention of dental diseases in children with disabilities.
Evaluation of efficacy of general anesthesia usage for dental diseases prevention in children with disabilities suffering from diseases of the central nervous system, blood diseases, respiration and mental disorders
Keywords: children with disabilities; general anesthesia; prophylaxis of dental diseases; sealing of fissures